Before the veil. - Nur Hanis Selamat. (2010)
Colour portraits of Muslim adolescent girls. My interest in photography began in portraiture. Living in a household where the majority is female, the portraits I have been producing have largely consisted of Muslim women. At the same time, the awkward transition phase between a child and adult has been a big fascination of mine and has influenced the direction of my photographic pursuits. Both themes have somehow managed to be present in most of my pictorial endeavours. In my final year project, I intend to merge and expand on both themes, which in turn creates a new exploration into the experiences of a Muslim female adolescent. Having gone through similar experiences, this project reflects my own personal experiences and feelings towards the issues that come with it.